Quran memorization tool based on the attention of High-Functioning Autistic using evolving living technology / Nur Madihah Jafar - Nur Madihah , Jafar (2017)
In sustaining HFAs’ attention during memorization the Quran verses is very challenging. Some of them suddenly switch to other activities, some of them still memorize the Quran verses but their eyes looking around or tapping the desk those give sorts of teachers’ perception either the students still learn or their attention has been distracted. Nowadays, education is evolving due to the technology advances. The use of technological teaching aids becomes trends in a classroom. However, existing apps specifically developed for the HFAs concerning the memorization of Quran verses are hard to find. Thus, this research project is expected contributing something to the education sector by inventing a tool that will be effective in solving the problem. Literature review, interview, and observation were done to consider several aspects in developing the Quran Memorization Tool (QMT). There are; the adaptation of abilities of sensors and actuation which are introduced in the EVLIT, the adaptation of Neurofeedback Training (NFT) approaches (visual feedback, audio feedback, verbal response, and rewards), the components involved such as learning emotions, selfrewarding, (selective attention, sustain attention, memorization skill), adjust brainwave, brainwave data, receive brainwave, and memorization session. The analysis of the experimental result with the HFAs showed that the HFAs’ attention performance was enhanced when they were rewarded with a video illustrates some abstract animation in the middle of distracted attention during the use of the QMT. It can be deduced that the invention of QMT is effective in enhancing the HFAs’ attention during memorization of the Quran verses.